Assessment of the Financial Stability of Russian Printing Companies: Business Services Sector# - Fedosova, Raisa; Lisovsky, Alexander; Yussuf, Anastasia; Panova, Svetlana; Zlotnikova, Galina (Journal of Reviews on Global Economics, 2018)
This article substantiates the necessity of assessing financial stability of printing companies involved in the business services sector. Peculiarities of business activities of today’s printing companies under current conditions have been revealed and financial stability levels of these companies, computed based on Edward Altman’s Z-score bankruptcy probability assessment model, have been defined. To analyze the status of printing companies involved in the business services sector, Altman’s methodology that is based on a five-factor model for predicting the insolvency risk of companies was applied. The analysis of the industry allowed us to distribute selected companies in three zones of bankruptcy. The number of companies in three bankruptcy zones as well as their share in the total scope of firms in the period under review was defined. Recommendations on the implementation of a set of measures in production and management structures of the assessed companies have been suggested. These measures allow the financial position of the companies in the industry to be maintained and strengthened. The results of this study may lay the foundation for further studies of urgent issues related to the analysis and evaluation of the financial sustainability level of printing companies.